EXTERNAL FACTORS OF DEVELOPMENT OF LEGAL SYSTEM OF RUSSIA (CONSTITUTIONAL BASES) - Levakin, Igor (Administrative and Criminal Justice, 2015)
The article describes the major modern political, economic, social and religious factors of the development of Russian legal system. Based on statistical and empirical materials, these or those factors highlighted as the main ones, but it presents an author's subjective point of view. According to the reasons mentioned above, the author describes the most important features of Russian legal system.